THE STORY OF INONG BALEE: A CASE STUDY ON BEGGAR FAMILIES IN BANDA ACEH - Taufiki, Riki; Fitria, Ida; Anwar, Ayu Fajri (Universitas Islam Negeri Ar-Raniry, 2016)
The current study explores the Inong Balee beggars, widows who have been left by their husbands who passed away. Their survival of living is through begging around with their fatherless children in the city of Banda Aceh. The objectives of this study are to identify the demographic condition of Inong Balee beggars, the reasons why inong balee beg, and the educational condition of their children. The study was conducted using a case study approach which includes observation, interviews, and document analysis. Data was collected from April 2012 to August 2012 in the city of Banda Aceh. Purposive sampling was used to select the informants. The interviews and observations were conducted with 12 informants consisting of Inong Baleebeggars and their children. The findings have shown that most of the beggars are from regions in Aceh, other than Banda Aceh and began begging in Banda Aceh after the Tsunami in 2004. Furthermore, the main reason for Inong Baleeto beg is because they become widows without a main source of income and need to increase the financial status of their family. The education condition of their children is notgood; some of them still go to school but do not get a quality education, while others have dropped out of school entirely. This study examines the current status of Inong Balee beggars in terms of social, economic, and educational conditions. The government of Aceh should put a larger focus on Inong baleein order to improve their lives.